2022
DOI: 10.1002/mcf2.10206
|View full text |Cite
|
Sign up to set email alerts
|

Examining Epibenthic Assemblages Associated with Artificial Reefs Using a Species Archetype Approach

Abstract: The placement of artificial reefs (ARs) influences, to various degrees, a wide range of epibenthic species, whereas most assessments focus on target or focal species. Methods of capturing the responses of many species can inform management about the full range of likely responses of species to the location and arrangement of ARs. Performing many single‐species analyses presents difficulties in interpretation. We used monitoring data from 14 surveys from June 2017 to August 2020 in an area with ARs deployed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Animal selection and description Yu et al (2022) grouped the epibenthic reef-dependent species found in a reef area located in Bohai, China, into six archetypes based on their shared responses to the environmental variables of temperature, DO, substrate type, and distance to the nearest reef. The six archetypes simplified the spatial distribution responses of multiple species to environmental conditions and ARs and offered representative reef-dependent species as indicators of community response.…”
Section: Introductionmentioning
confidence: 99%
“…Animal selection and description Yu et al (2022) grouped the epibenthic reef-dependent species found in a reef area located in Bohai, China, into six archetypes based on their shared responses to the environmental variables of temperature, DO, substrate type, and distance to the nearest reef. The six archetypes simplified the spatial distribution responses of multiple species to environmental conditions and ARs and offered representative reef-dependent species as indicators of community response.…”
Section: Introductionmentioning
confidence: 99%
“…In this, and the use of an ordination, isopam is similar to twinspan (Hill, 1979 ), but does not involve internal readjustments, uses geodesic distances (taking account of “neighbors of neighbors” in feature space), and works on multidimensional ordination spaces. It has been previously used for large‐scale classifications of forests (Cabido et al., 2018 ; Černý et al., 2015 ; Zeballos et al., 2020 ) and other systems (Feilhauer et al., 2021 ; Hein et al., 2014 ; Peterka et al., 2017 ; Yu et al., 2022 ). isopam can be run both unsupervised and supervised (with reference plots).…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously used for large-scale classifications of forests (Cabido et al, 2018;Černý et al, 2015;Zeballos et al, 2020) and other systems (Feilhauer et al, 2021;Hein et al, 2014;Peterka et al, 2017;Yu et al, 2022). isopam can be run both unsupervised and supervised (with reference plots).…”
Section: Isometric Partitioningmentioning
confidence: 99%